Activation of aPKCζ Toward TC10 is Regulated by High Fat Diet and Aerobic Exercise in Skeletal Muscle - Saito, M. (2008)
We determined whether chronic aerobic exercise reverses high-fat diet-induced impairments in the CAP (c-Cbl associated protein)/c-Cbl (Casitas b-lineage lymphoma) signaling cascade in rodent skeletal muscle. Sprague-Dawley rats were placed into either control (CON, n=16) or high-fat fed (n=32) diet groups for 4 wk. During a subsequent 4 wk experimental period 16 high-fat fed rats remained sedentary (HF), 16 high-fat fed rats completed 4 wk of exercise training (HFX), and CON animals were sedentary and remained on the control diet. Following the intervention period, animals were subjected to hind limb perfusions in the presence (n=8/group) or absence (n=8/group) of insulin. In the plasma membrane fractions, neither highfat feeding nor exercise training altered APS (adaptor protein with PH and SH2 domains), c-Cbl or TC10 protein concentrations. In contrast, CAP protein concentration and insulin-stimulated plasma membrane c-Cbl tyrosine phosphorylation were reduced by high-fat feeding, but exercise training reversed these impairments. Of note was that insulin-stimulated aPKC ζ (atypical protein kinase C) kinase activity toward TC10 was reduced by high-fat feeding but normalized by exercise training. We conclude that chronic 4 wk of exercise training can reverse high-fat diet-induced impairments on the CAP/c-Cbl pathway in high-fat fed rodent skeletal muscle. We also provide the first evidence that the CAP/c-Cbl insulin signaling cascade in skeletal muscle may directly interact with components of the classical (phosphoinositide 3-kinase dependent) insulin signaling cascade.